Metabolic profiling of apples from different production systems before and after controlled atmosphere (CA) storage studied by 1H high resolution-magic angle spinning (HR-MAS) NMR. (15th October 2017) - Vermathen, Martina; Marzorati, Mattia; Diserens, Gaëlle; Baumgartner, Daniel; Good, Claudia; Gasser, Franz; Vermathen, Peter
Highlights: High resolution magic angle spinning NMR provides apple metabolic fingerprints. All apple cultivars show similar metabolic drifts in controlled atmosphere storage. Metabolic changes during storage are relevant for fruit aroma and quality. Most metabolic differences between cultivars assimilate during storage. Fructose and phenolic compound-levels remain discriminant for BIO apples. Abstract: Determination of metabolic alterations in apples induced by such processes as different crop protection strategies or storage, are of interest to assess correlations with fruit quality or fruit disorders. Preliminary results proposed the metabolic discrimination of apples from organic (BIO), integrated (IP) and low-input (LI) production. To determine contributions of temporal metabolic developments and to define the type of metabolic changes during storage, 1 H high resolution-magic angle spinning (HR-MAS) NMR spectroscopy of apple pulp was performed before and after two time points of controlled atmosphere storage. Statistical analysis revealed similar metabolic changes over time for IP-, LI- and BIO-samples, mainly decreasing lipid and sucrose, and increasing fructose, glucose and acetaldehyde levels, which are potential contributors to fruit aroma. Across the production systems, BIO apples had consistently higher levels of fructose and monomeric phenolic compounds but lower levels of condensed polyphenols than LI and IP apples, while the remaining metabolites assimilated.